Forms of Interaction of the National Police with the Public in the Field of Ensuring Public Safety and Order - A. V. Komziuk (Bulletin of Kharkiv National University of Internal Affairs)
Interaction is a necessary and important part of the work of the National Police, including in the field of public safety and order. Due to the interaction we achieve the coordination of actions and joint activities of the National Police with other entities. Existing forms and methods of the interaction between the National Police and the public do not meet the current requirements and need to be refined or finding new forms and methods. Therefore, there is the need to conduct a thorough study of the problems of the interaction of the National Police with other entities of ensuring public safety and order.